Strand 1: Students at the Centre: Non-lineal Narratives and Self Conscious Learning - Pink, Sarah (Proceedings of the International Conference on Networked Learning, 1998)
This paper reflects on the design and evaluation of a multimedia learning tool developed for students of qualitative research at the University of Derby. This learning tool is intended for use as a networked learning tool supported by additional reading materials, face to face or e-mail tutorial and seminar support. It is situated as the key learning text for one topic in a ten topic module. I explore two issues pertinent to the introduction of multimedia networked learning cools into existing teaching and learning cultures. First, the concept of the nonlineal - in multimedia narratives, in the ethnographic research process, in the learning process and in relation to teaching strategies. In doing so I relate educational theory (in particular discussions of students' learning strategies and learning cultures) to social and cultural theory relating to subjectivity, identity and new communications technologies. With reference to the learning tool in question I discuss the multilinearity of ethnographic research experiences to argue that multimedia offers a format that in combination with other support is a compatible and coherent way to learn about research methodology. Second, drawing from evaluations of the multimedia tool I discuss the idea of self-conscious multilineal learning, and continuities between multimedia hypertext learning and conventional teaching and learning practices. Finally I relate the theoretical and practical implications of these discussions to the question of developing 'student centred learning'.